Stand up and shout out : women's fight for equal pay, equal rights, and equal opportunities in sports - Steidinger, Joan (Lanham, Maryland : Rowman & Littlefield, 2020)
"Today, women have greater opportunities to participate in sports than ever before, particularly due to the passage of Title IX in 1972. Yet, despite all this growth, women still struggle to hold leadership positions, become coaches of both girls and boys teams, receive equal pay, and get even adequate coverage in the media. [This book] explores the three crucial areas in sport that remain huge concerns for women: leadership, money, and media. Steidinger looks at the number of ways in which women experience vast inequalities by examining topics such as the politics of sport, sexual assault, the #MeToo movement, pay equity, women in coaching positions, and the experiences of women of color and LGBTQ athletes. Interviews with leading authorities in the field and prominent female athletes are interwoven throughout to add both expert and personal perspectives to the conversation. Stand Up and Shout Out does more than just inform readers about these important issues; its purpose is to create enlightened discussions around the unequal treatment of women and present readers with 'action steps' so we can all become active contributors toward improving this situation. This is an ideal time to fight for women's equality in sports, as it draws attention to the growing need for advocacy for girls and women around the world in all areas of life." --
Introduction -- Leading the charge -- Show us the money: striving for pay and funding equity -- Honoring our women athletes: where's the media coverage? -- The politics of women's sport: becoming an active part of the sports network -- Speaking up and promoting women coaches -- #MeToo Movement in sports: speaking up about sexual assault and abuse -- Double standards: prejudice and unequal treatment of women of color under Title IX -- The LGBTQ community: lesbian and transgender athletes -- A global challenge: international women in sport -- Time's up: primary concerns and action steps.
Includes bibliographical references (pages 165-197) and index.
Keywords: Sports for women -- Management; Sports for women -- Economic aspects; Sports for women -- Social aspects; Mass media and sports; Discrimination in sports; Gestion; Aspect social; Discrimination dans les sports; Discrimination in sports; Mass media and sports; Sports for women -- Management; Sports for women -- Social aspects